PENGARUH KEDISIPLINAN, LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DI BYSTORE SINGARAJA - Nopiyani, Putu Eka; Wahyuni, Kadek Dwi (Jurnal Daya Saing, 2024)
This research aims to determine the influence of discipline, work environment and work culture on employee performance at Bystore Singaraja. The data analysis technique used in this research is multiple linear regression analysis, classical assumption test, model feasibility test (Goodness of Fit), hypothesis testing, using the SPSS Version 21.0 for Windows application. The results of this research show that the influence of discipline has a positive and significant effect on employee performance at Bystore Singaraja with a t-count > t-table (3.734 > 1.693) with a significance level of 0.001 < 0.05. The work environment has a positive and significant effect on employee performance at Bystore Singaraja, t-count > t-table (2.210 > 1.693) with a significance level of 0.035 < 0.05. Work culture has a positive and significant effect on employee performance at Bystore Singaraja with t-count > t-table (2.699 > 1.693) with a significance level of 0.011 < 0.05. Based on the results of statistical test calculations, it is known that the value of F-count > F-table, (22.777 > 3.29), this indicates that discipline, work environment and work culture jointly influence employee performance with a significant level of 0.000 < 0.050.